HUBUNGAN EFIKASI DIRI DENGAN KEPATUHAN DIET 3J PADA PASIEN DIABETES MELITUS DI PUSKESMAS MANDAI KABUPATEN MAROS - Rizqah, Siti Fadhillah; Basri, H. Muh; Rahmatia, St. (STIKES Nani Hasanuddin Makassar, 2018)
The cause of illness and pain that occurs in the community because of the behavior of living less attention to healthy behavior. Which is also the main cause to the increasing number of people with diabetes mellitus, it is known that the main cause of people with diabetes mellitus is caused by individual life behavior.Objective: to know the relations between self efficacy with 3j diet adherence in patients with diabetes mellitus at PuskesmasMandaiMaros Regency. Method: correlational research with cross sectional design. The population in this study were all patients with diabetes mellitus as many as 65 patients.The sample in this research is 30 samples. It was analyzed using the chi square test with an alternative value of fisher's exact ?: 0.05. The results of the study: high self-efficacy as many as 22 respondents (73.3%) and low efficacy of 8 respondents (26.7%) while those who obeyed the 3j diet adherence were 24 respondents (80.0%) and those who did not obeythe diet 3j as many as 6 respondents (20.0%).The result of data analysis indicate that there is self efficacy relations with 3j diet adherence in patients with diabetes mellitus shown with p value = 0,002. Conclusion: There is a relations betweenself efficacy with 3j diet compliance in patients with diabetes mellitus at Puskesmas MandaiMaros Regency.